Antimicrobial Resistance Pattern of Gram-negative Bacteria Causing Urinary Tract Infection (Stamford Journal of Pharmaceutical Sciences, 2010)
Urinary tract infection (UTI) is a common and occasional recurrent bacterial illness with an increasing resistance to antimicrobials. Antibiotic resistance in UTI is a growing public health problem in the world including Bangladesh. The study objective was to examine the present incidence of UTIs in Bangladesh in a point period of time from January to December 2007. A retrospective data analysis of culture results of urinary pathogens was performed. The data was collected from the Clinical Microbiology Laboratory of International Centre for Diarrhoeal Disease Research, Bangladesh (ICDDR,B). The data included culture results of 9,854 urine samples and only Gram-negative isolates irrespective of age groups were analyzed. The prevalence of UTI was observed in 24.14%. It was observed that out of 2,379 uropathogens Escherichia coli (66.92%) was the most prevalent isolate followed by Klebsiella spp. (13.45%), Proteus spp. (6.77%) and Pseudomonas spp. (6.77%). The percentage of resistance to different antibiotics was higher in E. coli, Klebsiella spp. and Pseudomonas spp. isolates compared to that of others. Among the total number of isolates the resistant rate of E. coli and Klebsiella spp. to ampicillin was 86.09% and 83.33% and to cotrimoxazole was 67.61% and 59.81%, their resistance rate to nalidixic acid was 83.28% and 61.54%. All other isolates also showed above 80% resistance to ampicillin and above 50% to cotrimoxazole whereas imipenem was found to be the most effective against the uropathogens followed by amikacin. Key Words: Urinary tract infection; Antimicrobial resistance; Uropathogens; Bacteriuria; Gram-negative bacteria DOI: 10.3329/sjps.v2i1.5815Stamford Journal of Pharmaceutical Sciences Vol.2(1) 2009: 44-50